PHYSICAL EXERCISES AS A MEANS TO IMPROVE POSTURE OF FEMALE STUDENTS OF HIGHER TECHNICAL EDUCATIONAL INSTITUTIONS - Syrotynska, O. K. (Rehabilitation and Recreation, 2022)
The article gives recommendations about the application of physical exercises to improve the posture of female students of higher technical educational institutions which are based on the principles of regularity and compliance with execution technique. Analyzed and provided theoretical and practical knowledge that correct posture is one of those tasks to maintain their own health, which we do in childhood. If at a young age the importance of correct posture on the body is underestimated, with age, the problems of the back will become more urgent and can lead to serious health problems. Proper posture is not only beauty and grace, but also a healthy spine. Poor posture is not just an aesthetic problem, but a cause of back pain, headaches, tension in the neck and shoulder area, which will deliver constant discomfort and discomfort in everyday life. Before moving on to studying and improving the technique of performing a set of exercises to improve posture, we introduced the students to the basic rules that will help maintain the spine in a healthy state, namely: firstly, you need to monitor the correct posture constantly: when you walk, when you sit, when you stand; secondly, to maintain the correct posture, a strong muscular corset is required, therefore, the proposed set of exercises to improve posture is well combined with general physical training, exercises on the gymnastic ball, exercises to strengthen the abdominal muscles and back, and recreational swimming; try to move more during the day. Compliance with all these rules and the regular implementation of a set of physical exercises will help improve posture, which means keeping the spine healthy in later life.